Taxonomia das angiospermas aquáticas do reservatório de Itaipu, margem brasileira. - Soares, Witalo Cleidson Rodrigues (2024)
Taxonomic studies of the aquatic flora of reservoirs help in the conservation of biodiversity and in the implementation of measures for efficient management, regarding the management and monitoring of water resources. A taxonomic study of the aquatic angiosperms present in the Itaipu reservoir was carried out and the similarity of the floristic composition between its tributaries was evaluated. 235 points distributed in eight tributaries that supply the reservoir were covered. The expeditions took place in March and November 2023 and March and July 2024, visiting the coastal region of the tributaries, about five fragments of angiosperms that had sexual reproductive structures were collected. The specimens were herborized, identified, and then morphological descriptions, taxonomic comments were made, and data on the distribution, phenology, and habitat of the species were provided. Analyses were also carried out on the similarity of the composition of the community in the tributaries, using the Jaccard dissimilarity index and the Unweighted Arithmetic Mean Grouping (UPGMA) method. As a result, 67 species of aquatic angiosperms were identified, distributed among 24 families, with Cyperaceae being the most diverse, with 15 species, followed by Poaceae and Onagraceae, with 13 and six species, respectively. The São Francisco Falso and Arroio Guaçu rivers were the places with the highest richness, presenting 33 and 28 species, respectively. The most frequent biological types in the tributaries were amphibious and emergent plants, while in the reservoir, species of sporadic occurrence prevailed. The tributaries of the Itaipu reservoir, São João and São Vicente, as well as Ocoí and São Francisco Falso, showed greater similarity in the composition of their communities. The Itaipu reservoir has a great taxonomic diversity of aquatic angiosperms, with new records of species for the region, and it is of fundamental importance to continue monitoring this community for the conservation of local biodiversity, ensuring the environmental services provided by these organisms, such as improving water quality and nutrient cycling.